The relationship between phonological awareness and reading correctness and spelling errors - Rezhne Saefaddin Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The study is entitled (The relationship between phonological awareness and reading correctness and spelling errors). The sample of the research is the fourth-grade students, who were taken in two public schools for the academic year (2023-2024). Phonological level is an important foundation in the learning process and the first step in learning to read and write. In the Kurdistan Region, some students in educational centers at different stages suffer from spelling errors and reading deficiencies. The importance of this study is to identify that one of the causes of spelling errors and reading deficiencies is the deficiencies in learning sounds and how to express them at the beginning of the first stage of learning, in order to pay more attention to teaching the letters and how to pronounce them from the beginning of learning in schools, especially in the first grade. To obtain the results of the study relied on the descriptive approach of analysis, the aim of this research is to identify the relationship between phonological awareness and reading accuracy and spelling errors. The aim of this study is to answer several questions: Is phonological awareness related to spelling errors among the students of the study sample? Is phonological awareness related to reading accuracy among the students in the study sample? What are the most important common mistakes that the students in the study sample make in each of the areas of phonological awareness, spelling errors and reading accuracy? As a result, there is a strong relationship between phonological awareness and reading accuracy and the relationship between phonological awareness and spelling is strong and direct. The most important errors of students in all three aspects of phonological awareness, accuracy, reading and spelling are presented in the research. At the end of the research, some conclusions and a list of sources are presented.